2005
DOI: 10.1128/aem.71.3.1123-1129.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Degradation of Nonylphenol Isomers by Sphingomonas xenophaga Bayram

Abstract: Sphingomonas xenophaga Bayram, isolated from the activated sludge of a municipal wastewater treatment plant, was able to utilize 4-(1-ethyl-1,4-dimethylpentyl)phenol, one of the main isomers of technical nonylphenol mixtures, as a sole carbon and energy source. The isolate degraded 1 mg of 4-(1-ethyl-1,4-dimethylpentyl)phenol/ml in minimal medium within 1 week. Growth experiments with five nonylphenol isomers showed that the three isomers with quaternary benzylic carbon atoms [(1,1,2,4-tetramethylpentyl)phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
118
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 36 publications
7
118
1
Order By: Relevance
“…However, the latter isomers were cometabolically transformed in experiments in which growth isomers were present. Furthermore, differential degradation was clearly evident because isomers with a more highly branched alkyl side chain were degraded much faster than those with less complex branching (10).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…However, the latter isomers were cometabolically transformed in experiments in which growth isomers were present. Furthermore, differential degradation was clearly evident because isomers with a more highly branched alkyl side chain were degraded much faster than those with less complex branching (10).…”
mentioning
confidence: 91%
“…Growth experiments with strain Bayram showed that nonylphenol isomers with a quaternary carbon atom served as growth substrates, whereas the isomers containing one or two hydrogen atoms in benzylic position did not (10). However, the latter isomers were cometabolically transformed in experiments in which growth isomers were present.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The positive control for rag1 was CdCl 2 (Fluka), and for cyp1a1 1,5-dimethylnaphthalene (DMN; Fluka) was used. Exposure experiments were carried out using bisphenol A (BPA), 17b-estradiol (E2), and 17a-ethinylestradiol (EE2; Sigma-Aldrich; Buchs, Switzerland), atrazine and cyproconazol (Dr. Ehrenstorfer; Augsburg, Germany), and nonylphenol (NP) isomer 19 (4-NP 112; 4-(1-ethyl-1,4-dimethylpentyl)phenol; a generous gift from F. Gabriel, custom made; Gabriel et al, 2005).…”
Section: Chemicalsmentioning
confidence: 99%
“…They are attracting interest as a result of their high potential for bioremediation. In recent years, many Sphingomonas strains, which have been isolated from a variety of contaminated environments, have been described with respect to their ability to degrade xenobiotics and aromatic compounds, such as biphenyl (Fredrickson et al, 1995), dibenzo-p-dioxin (Wittich et al, 1992), carbazole (Habe et al, 2002), tetralin (Hernáez et al, 1999), pentachlorophenol (Saber & Crawford, 1985), 4-nonylphenol (Gabriel et al, 2005), c-hexachlorocyclohexane (Imai et al, 1989) and herbicides (Adkins, 1999;Kohler, 1999). In addition, Sphingomonas strains are often isolated from contaminated soils because of their ability to degrade polycyclic aromatic hydrocarbons (PAHs), which are ubiquitous environmental pollutants with toxic, mutagenic and carcinogenic properties (Bastiaens et al, 2000;Khan et al, 1996;Mueller et al, 1990;Pinyakong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%